PENGARUH MEDIA KALENDER TERHADAP PENGETAHUAN PENCEGAHAN NYERI MENSTRUASI (DISMENOREA) PADA REMAJA PUTRI (Politeknik Kesehatan Kemenkes Bandung, 2021)
Adolescents as the nation's next generation are expected to be healthy, the health expected of adolescents is overall health, both physically, mentally, socially, religiously and productively. Menstruation is a female reproductive cycle. Menstruation is usually accompanied by dysmenorrhea which can interfere with young women activities and reduce the individual's quality of life. In Indonesia, the incidence of primary dysmenorrhea is 54.89%. Dysmenorrhea itself if not handled quickly and appropriately can have an impact on activities for women, especially for young women. To determine the effect of calendar media on knowledge in preventing menstrual pain (dysmenorrhea). The method used in this research is the pre - experimental method with a one - group pre–test - post-test without control design with a total sample of 57 respondents who were selected using purposive sampling technique. The data analysis used was univariate analysis and bivariate analysis using the Paried T-test with a significance level of p value <0.05. There is an increase in knowledge of Pre Test and Post Test with a p value of 0.000 (<0.05). There is a significant effect between calendar media and young women knowledge of preventing menstrual pain (dysmenorrhea) in Sekejati Village, Bandung City.